Towards green growth (Paris, 2011)
"The Green Growth Strategy, outlined in this book, provides concrete recommendations and measurement tools to support countries’ efforts to achieve economic growth and development, while at the same time ensure that natural assets continue to provide the ecosystem services on which our well being relies. The strategy proposes a flexible policy framework that can be tailored to different country circumstances and stages of development. "